2017
DOI: 10.1111/1750-3841.13708
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Jian Carp (Cyprinus Carpio Var. Jian) Cathepsin B: Cloning, Expression, Characterization, and Antibody Preparation

Abstract: Cathepsin B (CatB) cDNA of 759 bp from Jian carp (Cyprinus carpio var. Jian) with amino acid similarity of 99.6% to common carp was cloned. The mature CatB was expressed in Escherichia coli BL21 transferred with vector CatB-pET-30a. It was purified and identified as a single band (29 kDa) on SDS-PAGE. Optimum CatB activity was observed at 40 °C and pH 5.5. Mouse anti-CatB polyclonal antibody with a high titer of 1:256000 was prepared successfully and shown to specifically recognize the antigen both in prokaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Embedded tissues were finally sectioned into 10 μm sections (three sections for each embedded tissue) with a Cryostat Microtome (CM1900-1-1, Leica Biosystems, Wetzlar, Germany). Immunohistochemical staining was then conducted as described in our previous research. , The first antibody was the HmCystatin C antibody (1:500 diluted), and the secondary antibody was a biotinylated antimouse IgG from goat (1:5 000 diluted; Beyotime Biotechnology, Shanghai, China). Endogenous peroxidase deactivation, blocking, and washing were routinely performed following the instructions of the Ultrasensitive SP (Mouse/Rabbit) IHC Kit (Maixin Biotechnology, Fujian, China).…”
Section: Methodsmentioning
confidence: 99%
“…Embedded tissues were finally sectioned into 10 μm sections (three sections for each embedded tissue) with a Cryostat Microtome (CM1900-1-1, Leica Biosystems, Wetzlar, Germany). Immunohistochemical staining was then conducted as described in our previous research. , The first antibody was the HmCystatin C antibody (1:500 diluted), and the secondary antibody was a biotinylated antimouse IgG from goat (1:5 000 diluted; Beyotime Biotechnology, Shanghai, China). Endogenous peroxidase deactivation, blocking, and washing were routinely performed following the instructions of the Ultrasensitive SP (Mouse/Rabbit) IHC Kit (Maixin Biotechnology, Fujian, China).…”
Section: Methodsmentioning
confidence: 99%
“…The contribution of collagen to meat texture has long been recognised, which is closely related to its amount, distribution, and degree of cross‐linking 32 . The crosslinked structure within collagen tightly connects the fibres, interweaving them into a stable network structure with enhanced toughness and mechanical strength 5,11,44 . Comparisons among species have shown that fish species with relatively firmer fillets had higher collagen fibril density within connective tissue 45 .…”
Section: Main Muscle Components Involved In the Development Of Flesh ...mentioning
confidence: 99%
“…32 The crosslinked structure within collagen tightly connects the fibres, interweaving them into a stable network structure with enhanced toughness and mechanical strength. 5,11,44 Comparisons among species have shown that fish species with relatively firmer fillets had higher collagen fibril density within connective tissue. 45 Furthermore, Hatae et al 46 assessed the contribution of collagens on the flesh texture in five fish species and noted a significant positive relationship between flesh firmness and collagen contents in the raw fillet.…”
Section: Relationship Between Collagen and Flesh Texturementioning
confidence: 99%